Effect of empagliflozin on exercise ability and symptoms in heart failure patients with reduced and preserved ejection fraction, with and without type 2 diabetes. (22nd December 2020) - Abraham, William T; Lindenfeld, JoAnn; Ponikowski, Piotr; Agostoni, Piergiuseppe; Butler, Javed; Desai, Akshay S; Filippatos, Gerasimos; Gniot, Jacek; Fu, Michael; Gullestad, Lars; Howlett, Jonathan G; Nicholls, Stephen J; et al.
Abstract: Aims: The EMPERIAL (Effect of EMPagliflozin on ExeRcise ability and HF symptoms In patients with chronic heArt faiLure) trials evaluated the effects of empagliflozin on exercise ability and patient-reported outcomes in heart failure (HF) with reduced and preserved ejection fraction (EF), with and without type 2 diabetes (T2D), reporting, for the first time, the effects of sodium-glucose co-transporter-2 inhibition in HF with preserved EF (HFpEF). Methods and results: HF patients with reduced EF (HFrEF) (≤40%, N = 312, EMPERIAL-Reduced) or preserved EF (>40%, N = 315, EMPERIAL-Preserved), with and without T2D, were randomized to empagliflozin 10 mg or placebo for 12 weeks. The primary endpoint was 6-minute walk test distance (6MWTD) change to Week 12. Key secondary endpoints included Kansas City Cardiomyopathy Questionnaire Total Symptom Score (KCCQ-TSS) and Chronic Heart Failure Questionnaire Self-Administered Standardized format (CHQ-SAS) dyspnoea score. 6MWTD median (95% confidence interval) differences, empagliflozin vs. placebo, at Week 12 were −4.0 m (−16.0, 6.0; P = 0.42) and 4.0 m (−5.0, 13.0; P = 0.37) in EMPERIAL-Reduced and EMPERIAL-Preserved, respectively. As the primary endpoint was non-significant, all secondary endpoints were considered exploratory. Changes in KCCQ-TSS and CHQ-SAS dyspnoea score were non-significant. Improvements with empagliflozin in exploratory pre-specified analyses of KCCQ-TSS responder rates, congestion score, and diuretic use in EMPERIAL-Reduced are hypothesis generating. Empagliflozin adverse events were consistent with those previously reported. Conclusion: The primary outcome for both trials was neutral. Empagliflozin was well tolerated in HF patients, with and without T2D, with a safety profile consistent with that previously reported in T2D. Hypothesis-generating improvements in exploratory analyses of secondary endpoints with empagliflozin in HFrEF were observed. Graphical Abstract: